Barriers to the provision of respectful maternity care during childbirth by midwives in South-West, Nigeria: Findings from semi-structured interviews with midwives - Waleola Bukola Ige; Winnie Baphumelele Cele (Elsevier, 2022)
Background: Disrespect and Abusive Care (DA&C) of women in health facilities during childbirth is a topic of growing concern globally. Given that DA&C is a violation of women's basic rights and a deterrent to facility-based maternity services for women. In Nigeria, limited evidence exists on barriers to the provision of Respectful Maternity Care (RMC), especially in South-West, Nigeria. Aim: This study aimed to explore the barriers to the provision of Respectful Maternity Care (RMC) during childbirth by midwives in selected health facilities in Lagos State, Nigeria. Methodology: The research used an Exploratory Descriptive Research Design. Data was collected through semi-structured individual interviews. Data analysis was done following Burns and Clarke's thematic method. Twenty midwives were purposively selected from two public secondary health facilities. Findings: The findings of this study revealed the barriers to the provision of RMC are diverse and interwoven. The study highlighted health system factors, health provider factors and client factors as barriers challenging the provision of RMC. Health system factors include physical structure of the labour ward, shortage of staff, shortage of resources, lack of motivation, hospital policy and poor working conditions. Health provider factors identified were midwives' personal beliefs, individual personalities, the poor orientation of professional staff, and poor collaborations among professionals. The client factors were women's/relations attitudes and unmet expectations. Conclusion: Training midwives and others on RMC without addressing deficiencies in the health care system will not achieve the desired goals of RMC. Encouraging teamwork, trust-building, collaboration, accountability and effective communication among health workers, policymakers, stakeholders and women will further promote RMC.